The effect of residual mechanical stresses and vacancy defects on the diffusion expansion of the damaged layer during irradiation of BeO ceramics - Ryskulov, Azamat E.; Ivanov, Igor A.; Kozlovskiy, Artem L.; Konuhova, Marina (Elsevier B.V., 2024)
The paper presents the results of a study on the application of Raman and UV spectroscopy methods to determine the structural damage kinetics in the near-surface layer of BeO ceramics caused by high-dose irradiation with He2+ ions. Interest in this type of ceramics is due to the combination of its structural and thermophysical parameters, making these ceramics one of the promising classes of materials for microelectronics and structural materials for nuclear reactors, with the possibility of operation in conditions of heightened radiation background. According to the conducted studies, it was established that with the irradiation fluence growth, changes in the nature of deformation structural distortions associated with the accumulation of residual mechanical stresses of tensile and compressive types are observed. At irradiation fluences of 1016–5 × 1016 Не2+/cm2, tensile stresses play a dominant role in structural distortions, while the value of compressive stresses at fluence growth makes up a small share in the overall nature of the deformations. Moreover, an elevation in the irradiation fluence above 5 × 1016 He2+/cm2 leads to a rise in the concentration of defects caused by the formation of oxygen vacancies, as well as He-VO type complexes, the presence of which is indicated by the halo intensity growth in the Raman spectra, as well as a change in the intensity of the absorption bands. Analysis of changes in thermophysical parameters revealed that a rise in structural distortions associated with the accumulation of complex defects results in thermal conductivity reduction and a deterioration in heat transfer processes associated with partial amorphization of the damaged layer. Moreover, the established direct relationship between the value of residual mechanical stresses and the degradation of thermal conductivity indicates the cumulative effect of destructive changes caused by irradiation, as well as the influence of diffusion mechanisms on the damaged layer thickness growth. © 2024 The Author(s) --//-- This is an open-access article Azamat E. Ryskulov, Igor A. Ivanov, Artem L. Kozlovskiy, Marina Konuhova, The effect of residual mechanical stresses and vacancy defects on the diffusion expansion of the damaged layer during irradiation of BeO ceramics, Optical Materials: X, Volume 24, 2024, 100375, ISSN 2590-1478, https://doi.org/10.1016/j.omx.2024.100375.
This work has been funded by the Science Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (Grant No. AP19579128). In addition, M. K was supported by EUROfusion Enabling Research Project ENR-MAT.02. ISSP-UL- “New dielectric functional materials and interfaces (DFMI) – Theoretical and Experimental analysis.” This work has been carried out within the framework of the EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (Grant Agreement No 101052200 — EUROfusion). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Commission. Neither the European Union nor the European Commission can be held responsible for them. The research was performed in theCenter of Excellence of the Institute of Solid-State Physics, University of Latvia, supported through European Unions Horizon 2020 Framework Programme H2020- WIDESPREAD- 01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; BeO ceramics; Disordering; Optical density; Optical transmittance; Radiation defects